2009
DOI: 10.4278/ajhp.071025115
|View full text |Cite
|
Sign up to set email alerts
|

3 For Life: A Model Pilot Program to Prevent Hepatitis B Virus Infection and Liver Cancer in Asian and Pacific Islander Americans

Abstract: Lessons learned from this pilot program have been used toward successful replication in other cities, demonstrating that 3 For Life is an accessible, affordable, reproducible, and sustainable model to increase HBV awareness, testing, and prevention among API adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…These rates were based on an analysis of newly screened participants– a group that was found to provide more generalizable prevalence estimates. 4,11 These estimates, which were higher than rates reported in other areas of the United States, 22,23 have been cited in the CDC recommendations3 and the Institute of Medicine report. 2 …”
Section: Program Assessmentmentioning
confidence: 95%
“…These rates were based on an analysis of newly screened participants– a group that was found to provide more generalizable prevalence estimates. 4,11 These estimates, which were higher than rates reported in other areas of the United States, 22,23 have been cited in the CDC recommendations3 and the Institute of Medicine report. 2 …”
Section: Program Assessmentmentioning
confidence: 95%
“…For example, in a study comparing community mobilization versus media campaigns in a campaign to promote hepatitis B vaccinations among Vietnamese-American children, investigators found that both media education and community mobilization successfully increased the number of Vietnamese-American children vaccinated [10]. Others have used community health promoters and lay health workers [10]; student-led educational workshops [11]; low-cost, affordable screening, and vaccinations [12]; and direct mailings of audiovisual and print materials [2, 10]. Although the effectiveness of these particular interventions has been studied, there is a lack of in-depth analysis on health communication and narrative practices used to effectively outreach to Asian Americans.…”
Section: Educational Entertaining and Culturally Sensitive Narrativmentioning
confidence: 99%
“…Less than 1% of general US population has hepatitis B; however, it is estimated that one in ten Asian Americans are infected [2]. The city and county of San Francisco has the highest rate of liver cancer in America and a disproportionate burden of undetected HBV infection due to the large Asian American population (about one third [3]) and high rates of HBV infection [4].…”
mentioning
confidence: 99%
“…Hepatitis B virus (HBV) infection is endemic in most Asian countries 57. Therefore, it is not surprising that the rate of chronic HBV infection among Chinese immigrants to North America is over 10 times the general population rate of less than 0.5% 8. In Asian countries, HBV transmission usually occurs vertically from mother to child at birth.…”
mentioning
confidence: 99%